Breaking and Believing: The Reflexive Journey of Muslim Identity in Mafi’s A Very Large Expanse of Sea - Ellita Permata; Yinghuei Chen (UIN Syarif Hidayatullah Jakarta, 2026)
In an era saturated and disrupted by persistent Islamophobia and cultural polarization, nuanced representations of how diasporic Muslim youth navigate and negotiate their subjectivities are increasingly critical. Through the lens of Anthony Giddens’s reflexive modernity, this study demonstrates the selective reconstruction of the Muslim identity in A Very Large Expanse of Sea (2018) by Tahereh Mafi. Using qualitative textual analysis and thematic analysis, the objective of the study is to examine how Shirin negotiates her identity in terms of religion, the hijab, cultural participation, and interpersonal relationships. The research reveals that Shirin’s identity is not merely inherited nor entirely rejected; she reconstructs it selectively, using cultural and religious practices as a means of self-assertion against the structural constraints of post-9/11 Islamophobia and the surveillance of her high school. The further analysis depicts her identity formation marked by the moment of continuous tension between resistance and negotiation, revealing the multiple realities of diasporic experience in late modernity. This study extends the previous literature on Muslim identity by employing Giddens’s reflexive modernity to argue that Muslim identities are selectively reconstructed in and through everyday practice instead of mainly through resistance or hybridity. It contributes to current literary and cultural studies by foregrounding young adult literature as a site for representing complex Muslim subjectivities.